Integrated production and safety risk management on farms - Leppälä, Jarkko (es, 2012)
Food production on farms is facing increasing demands and risks. Self-assessment tools for managing the primary food production social risks are needed to follow the requirements of the current Food Act in EU. The integrated identification of different types of risks on farms, such as production safety, assets, environmental and occupational health and safety risks, give useful information for the farm managers and stakeholders about farm production capacity and ability. In this study, integrated risk identification method was used to evaluate production and occupational health and safety risks on a dairy farm. The force field analysis was used to compare the farm manager views on farm milking process and its occupational health and safety risks. The case analysis identified factors and tasks that are critical to the farm occupational health and production safety. It can be seen as an example of integrated risk management tool used on the farm case.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; työturvallisuus; maataloustyö; risk; management; safety at work; farms